Off-budget and Tax Expenditures - Kraan, Dirk-Jan (OECD Publishing, 2006)
This paper reports the work that has been done by the OECD Secretariat on the project on off-budget and tax expenditures. The paper makes use of information that was provided at an expert meeting held in Paris in February 2004